Peningkatan Keterampilan Masyarakat Kelurahan Karang Joang Balikpapan Melalui Kegiatan Budidaya Ikan Dalam Ember (Budikdamber) - Cut Keumala Banaget; Eka Masrifatus Anifah; Barokatun Hasanah; Muhammad Fajar Sidiq; Yehezkiel Wijaya Oey; Abdul Rohim; Indah Putri Aulia (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2023)
The loss of food production land due to land conversion in supporting more economically profitable activities has urged innovations in agricultural and fishery activities by utilizing narrow land. A suitable method to solve this problem is Budikdamber or fish farming in a bucket. This method adopts the concept of aquaponics, which is a combination of aquaculture and hydroponics. Community skills improvement by Budikdamber activity aims to introduce a simple method for growing kale and catfish farming on narrow land using buckets so that people can obtain food directly from their yards. The target community for this activity is the residents of RT 14, Karang Joang Village. The implementation method includes field surveys and problem identification, formulation of solutions, implementation, monitoring, and evaluation. These steps are expected to provide skills for the community to do Budikdamber. The community showed positive responses to this activity. The community showed their understanding and opinion of the Budikdamber activity and the continuity of this activity.